Collaborative Governance dalam Kebijakan Sertifikasi Produksi Pangan Industri Rumah Tangga Kopi Bubuk Koto Tuo Kabupaten Tanah Datar - Hendri Koeswara; Desna Aromatica; Malse Yulivestra; Muhammad Ichsan Kabullah; Roza Liesmana; Enggi Hidayat (Jurnal Administrasi dan Kebijakan Publik, 2020)
The facilitation in the implementation of the Ground Coffee Home Food Industry (IRTP) certification policy by Tanah Datar District has not been optimal. This situation is counterproductive, with Nagari Koto Tuo being listed as one of the largest producers of ground coffee in Tanah Datar Regency. Nearly 75% of the Nagari Koto Tuo people live from processing coffee from generation to generation for more than two generations. A total of 160 Ground Coffee IRTPs with 177 coffee trademarks are registered in Nagari Koto Tuo, ironically only 14 have SPP-IRT. The policy issued by BPOM RI No. 22/2018 for the ease of providing the Home Industry Food Production Certificate (SPP-IRT) has not been able to respond in policy by the Regency Governments. The Nagari Koto Tuo government is also limited in advocating for Ground Coffee IRTP. And, since the launch of the Village Fund, there have not been many programs/and budgets allocated related to this Nagari, coupled with the existence of Nagari Owned Enterprises (BUMNag), which do not have a core business according to the village potential, namely coffee. Research using qualitative methods with a case study approach to collaborative governance was conducted by identifying the involvement of actors and policies in providing IRTP for Ground Coffee. The collaborative governance model removes the barriers of actors related to synergy and policies that have been blocked in their respective powers and duties and their respective functions that nullify the society's potential. Collaboration between actors has proven to be an important element in the success of providing SPP-IRTP for Ground Coffee by optimizing socio-economic capital in village development. This is where the obstacles that occur that cause a lack of IRT-P.